Husband and wife tearfully receive Posthumous Award for son - Nor Salwana, Mohammad Idris (2022)
KUANTAN, 17 March 2022 - No words uttered by husband and wife duo when receiving their late son’s degree at the 15th Universiti Malaysia Pahang (UMP) Convocation Ceremony at Dewan Jubli Perak Sultan Haji Ahmad Shah, here.